Selection of Priority Cause and Effect Chains on the Strategy Map of Goals Using AHP Multiple Criteria Analysis - PeniÄ‡, Sanja (Information Management and Business Review, 2014)
Today, when the labor market is extremely dynamic, and there is great competition, a certain level of knowledge is expected of every individual. This has influenced an increase in the number of higher education institutions, primarily in the private sector. To cope better with the growing global competition, the management of private higher education institutions is becoming increasingly aware of the needs to select the appropriate management methods. That would ensure the achievement of strategic goals and make a unique and clear methodology, easily applicable in today’s turbulent environment. The paper proposes a unique management methodology which would represent a strategic management framework applicable to most private higher education institutions. The creation of a strategy map of goals by linking SWOT and BSC methods with multiple criteria decision method is described. An emphasis is placed on the application of the multiple criteria decision-making method in the objective selection of priority cause and effect chains in the BSC strategy map. The result of the application of the proposed methodological framework targets the priority cause and effect chains, i.e. strategies which would enable the achievement of vision and mission.